Persepsi Dan Minat Mahasiswa Fakultas Pertanian Universitas Sam Ratulangi Terhadap Profesi Petani - Faradila, Violeta; Pangemanan, Lyndon Reindhart Jacob; Tambas, Jane Sulinda (Jurusan Sosial Ekonomi Pertanian, Fakultas Pertanian Universitas Sam Ratulangi, Manado, 2024)
This research aims to analyze the perception and interest of Agriculture Faculty students at Sam Ratulangi Universit toward the farming profession. Perception is assessedb based on income and work comfort, while interest is measured by feelings of enjoyment and desire. The research was conducted from April 2024 to Juni 2024. The data used includes both primary and secondary data. Primary data was directly obtained from respondents through surveys using prepared questionnaires, while secondary data was gathered from other relevant information related to this study. The research shows a positive perception and high interest from the Agriculture faculty students at Sam Ratulangi University towards the farming profession with a total perception score of 2.971 (87,80%) and a total interest score of 2.821 (83,36%). The relationship between perception and interest variables indicates a moderate and positive correlation with a value of 0,439, suggesting that a positive perception does not always result in a high level of interest.